2003
DOI: 10.1590/s0103-90162003000400006
|View full text |Cite
|
Sign up to set email alerts
|

Colored polyethylene soil covers and grafting effects on cucumber flowering and yield

Abstract: Cucumber (Cucumis sativus L.) is one of the most cultivated vegetable crops in plastic greenhouses in Brazil because of the short cycle and its high economic value in off-season harvests. To better understand this management technique the effect of different colored polyethylene soil covers was evaluated in relation to flowering and yield of the hybrid cucumber 'Yoshinari' grafted or not on the hybrid squash 'Ikky'. The polyethylene cover colors were black, white on black and green plus a control without cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…These resulted in enhancement of soil environment around roots of sweet pepper plants that led to enhancing plant growth, and hence improve nutrient absorption and uptake (Abdrabbo et al, 2009). These results were in line with those obtained by Pan et al (1999); Fonsecal et al (2003). Optimal root zone temperature with availability of water allow for adequate root function including better uptake of water and nutrients.…”
Section: Plant Elemental Contentsupporting
confidence: 90%
“…These resulted in enhancement of soil environment around roots of sweet pepper plants that led to enhancing plant growth, and hence improve nutrient absorption and uptake (Abdrabbo et al, 2009). These results were in line with those obtained by Pan et al (1999); Fonsecal et al (2003). Optimal root zone temperature with availability of water allow for adequate root function including better uptake of water and nutrients.…”
Section: Plant Elemental Contentsupporting
confidence: 90%
“…The use of different colours of polyethylene as soil cover for cucumber has been used mainly in many regions. The crop varies in response to polyethylene mulch covers depending on cultivar, materials used and environmental conditions [1,2,3]. Alenazi et.al., [4] reported that mulching and irrigation water management is among the dynamic practices that are being applied in commercial vegetable production.…”
Section: Introductionmentioning
confidence: 99%
“…The region experiences extreme cold during January and February, when maximum and minimum temperature falls below 22°C and 8°C respectively, average being around 13°C. Cucumber is susceptible to low temperatures throughout its growth cycle [4,5]. Cucumber cultivators of the district Cooch Behar also have similar experiences i.e.…”
Section: Introductionmentioning
confidence: 99%